PGC-1α regulates critical period onset/closure, mediating cortical plasticity - Zhang, Wei-Jun; Shi, Hou-Zhen; Guo, Mei-Na; Xu, Long-Fei; Zhai, Hong-Ru; Liu, Zi-Zhong; Zhu, Yong-Qiang; Zhang, Wei-Ning; Wang, Jia (Frontiers in Molecular Neuroscience, 2023)
Peroxisome proliferator-activated receptor PPARγ coactivator-α (PGC-1α) is concentrated in inhibitory interneurons and plays a vital role in neuropsychiatric diseases. We previously reported some characteristic features of schizophrenia (SZ) in GABAergic neuron-specific Pgc-1alpha knockout (KO) mice (Dlx5/6-Cre: Pgc−1alphaf/f). However, there is a fundamental gap in the molecular mechanism by which the Pgc-1alpha gene is involved in the neurobehavioral abnormalities of SZ. The loss of critical period (CP) triggers–maturations of parvalbumin interneurons (PVIs) and brakes—and the formation of perineuronal nets (PNNs) implicates mistimed trajectories during adult brain development. In this study, using the Pgc-1alpha KO mouse line, we investigated the association of Pgc-1alpha gene deletion with SZ-like behavioral deficits, PVI maturation, PNN integrity and synaptic ultrastructure. These findings suggest that Pgc-1alpha gene deletion resulted in a failure of CP onset and closure, thereby prolonging cortical plasticity timing. To determine whether the manipulation of the PNN structure is a potential method of altering neuronal plasticity, GM6001, a broad-spectrum matrix metalloproteinase (MMP)-inhibitor was applied. Here we confirmed that the treatment could effectively correct the CP plasticity window and ameliorate the synaptic ultrastructure in the Pgc-1alpha KO brain. Moreover, the intervention effect on neuronal plasticity was followed by the rescue of short-term habituation deficits and the mitigation of aberrant salience, which are some characteristic features of SZ. Taken collectively, these findings suggest that the role of PGC-1α in regulating cortical plasticity is mediated, at least partially, through the regulation of CP onset/closure. Strategically introduced reinforcement of molecular brakes may be a novel preventive therapy for psychiatric disorders associated with PGC-1α dysregulation.